Proses Pemberian ASI pada Ibu Berusia Remaja: Studi Fenomenologi Interpretatif - Vetty Priscilla; Ira Mulya Sari; Hermalinda Hermalinda (Ners Jurnal Keperawatan, 2024)
The current percentage of exclusive breastfeeding in West Sumatra is still below the national rate. Teenage mothers contribute to the low percentage of exclusive breastfeeding coverage. Young age is one of the factors that make it difficult to maintain breastfeeding behavior. The purpose of this study was to interpret the breastfeeding process among adolescent mothers. This study used a qualitative research design with an interpretative phenomenological approach to explore the breastfeeding process of adolescent mothers. Data were collected through in-depth interviews using semi-structured questions and analyzed with thematic analisysby using a seven-step interpretative phenomenological analysis approach. The results identified five themes, namely: 1) perceived support from health workers, 2) reasons for teenage mothers to give other foods/drinks besides breast milk, 3) teenage mothers' perceptions of family support in breastfeeding, 4) emotional feelings of teenage mothers when breastfeeding, and 5) obstacles encountered by teenage mothers when breastfeeding.Suggestions The practice of breastfeeding by adolescent mothers provides an understanding that breastfeeding in adolescence has many challenges and barriers. Appropriate intervention strategies are needed to improve the understanding of adolescent mothers during the breastfeeding process so that breastfeeding success is achieved. Keywords: Adolescent Mothers, Breastfeeding, Exclusive Breastfeeding, Qualitative